2014
DOI: 10.1016/j.toxrep.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of styrene oligomers extracted from polystyrene intended for use in contact with food

Abstract: HighlightsWe evaluated the genotoxicity of styrene oligomers extracted from polystyrene intended for use in contact with food.Compared with 50% ethanol, acetone extracted a far greater amount of styrene dimers and trimers from polystyrene.Ames tests and an in vitro chromosomal aberration test were negative.The risk of the genotoxicity of styrene oligomers migrated from polystyrene food packaging into food is likely very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…Except for the CA, which was performed with Chinese hamster lung cells (CHL), all assays were conducted with human cell lines. Out of the 11 studies analyzed here, two [102,103] applied exogenous metabolic activation while other bioassays were metabolically competent [104]. No information was available for the other studies.…”
Section: Genotoxicity Testing Of Fcms With Mammalian In Vitro Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the CA, which was performed with Chinese hamster lung cells (CHL), all assays were conducted with human cell lines. Out of the 11 studies analyzed here, two [102,103] applied exogenous metabolic activation while other bioassays were metabolically competent [104]. No information was available for the other studies.…”
Section: Genotoxicity Testing Of Fcms With Mammalian In Vitro Assaysmentioning
confidence: 99%
“…Only negative results were scored by studies with the MN [107,108], the BlueScreen TM HC [102], the CA [103], and the SCE [109]. The p53 CALUX ® was able to detect possible genotoxic effects in a study with samples such as a pizza box and paperboard with printing inks [110].…”
Section: Genotoxicity Testing Of Fcms With Mammalian In Vitro Assaysmentioning
confidence: 99%
“…The tentatively identified compound 1e-Phenyl-4e-(1phenylethyl)-tetralin, in fractions 9 to15 of pooled HIPS and blank HIPS, was found to be a styrene trimer of polystyrene and has been detected in extracts of sediments as residues of PS contamination (Hong et al, 2016), as well as in food packaging materials (Choi et al, 2005;Nakai et al, 2014). Some styrene trimers have been reported as weak AhR agonists (Hong et al, 2016), and it is possible that 1e-Phenyl-4e-(1phenylethyl)-tetralin contributed to the AhR-mediated response in fractions 12 and 14 of pooled HIPS, and fraction 12 of blank HIPS.…”
Section: Chemical Analysis Of Fractionated Pooled Plastic Extracts Bymentioning
confidence: 99%
“…Most PET bottles used for retailing palm wine have a polystyrene cap, which is a safety concern if styrene migrates to the drink. An in vitro genotoxicity investigation to evaluate the genotoxicity of styrene oligomers extracted from polystyrene intended for use in contact with food has been conducted [18], and it was concluded that the risk of the genotoxicity of styrene oligomers migrating from polystyrene food packaging into food is likely very low.…”
Section: Styrenementioning
confidence: 99%